The fate and mobility of chromium, arsenic and zinc in municipal sewage sludge during the co-pyrolysis process with organic and inorganic chlorides - Mahboub Saffari; Masomeh Moazallahi; Rezvan Mashayekhi (Scientific Reports)
Abstract Co-pyrolysis is an efficient approach for municipal sewage sludge (SS) treatment, facilitating the production of biochar and promoting the stabilization and removal of heavy metals, particularly when combined with chlorinated materials. This study explores the impact of pyrolysis temperatures (400 °C and 600 °C) and chlorinated additives (polyvinyl chloride (PVC) as an organic chloride source and ferric chloride (FeCl3) as an inorganic chloride source) at 10% and 20% concentrations, on the yield, chemical speciation, leachability, and ecological risks of arsenic (As), chromium (Cr), and zinc (Zn) in biochar derived from SS. The results revealed that increasing the pyrolysis temperature from 400 to 600 °C significantly reduced biochar yield due to enhanced volatilization of organic components, as well as the removal of heavy metals in interaction with chlorinated materials. Chlorinated additives distinctly influenced heavy metal behavior. PVC treatments at 600 °C effectively reduced the total concentrations of As and Zn by 60% and 88.3%, respectively, while FeCl3 reduced Cr concentrations by up to 72.5%. Chemical speciation analysis showed that PVC treatments increased the residual fractions of As and Zn, reducing their bioavailability and environmental risk. In contrast, FeCl3 promoted the transformation of Cr into oxidizable fractions, enhancing its stability. TCLP results confirmed the effectiveness of both additives in reducing heavy metal leachability, with PVC at 600 °C demonstrating superior performance for As and Zn, and FeCl3 excelling in Cr stabilization. Ecological risk index assessments revealed that PVC treatments consistently resulted in lower RI values at both temperatures and concentrations, keeping them below the low-risk threshold. In contrast, FeCl3 treatments exhibited elevated risk levels, especially at higher concentrations and temperatures, reaching moderate to considerable risk categories. Overall, PVC treatment at 600 °C proved to be the most effective strategy for reducing As and Zn leachability and enhancing biochar stability. While FeCl3 demonstrated better performance in Cr stabilization, these findings highlight the importance of selecting appropriate chlorinated additives based on the target heavy metal for optimizing biochar production and minimizing environmental impacts effectively.